Diagnostic Evaluation of Cervical Lymphadenopathy in FNAC Samples: Case Based Study in A Rural Tertiary Care Hospital - Harikrishnan, Volga; Sonti, Sulochana; Srinivasan, Chitra (Annals of Pathology and Laboratory Medicine, 2019)
Background: Nowadays lymphadenopathy is a common clinical problem and it may be in a form of localized, limited, or generalized. Cervical lymphadenopathy can be due to infections, malignancies, autoimmune disorders and other miscellaneous conditions. To diagnose lymphadenopathy in a short time, a simple, cost-effective outpatient procedure Fine needle aspiration cytology (FNAC) is necessary. FNAC is an accurate procedure to diagnose lymphadenopathy cases. The purpose of the study was to evaluate the results of FNAC of nodes especially cervical lymphnodes in our institution. Methods: A retrospective analysis of cervical lymphadenopathy cases reported by FNAC procedure over the period of six months in Department of Pathology. Smears were stained with four different stains including Hematoxylin and Eosin stain, Papaniculaou stain and Giemsa stain. In suspected cases of Tuberculosis special stain like Ziehl-neelsen were performed Result: In this study age of the patient varied between 1 to 70 years. Most of the cases were benign in which reactive lymphoid hyperplasia was the leading one. The remaining cases were metastatic carcinoma which includes poorly differentiated carcinoma with unknown primary, squamous cell carcinoma (SCC) (Primary from carcinoma cervix, cheek and tongue), adenocarcinoma (Primary from lung and gastrointestinal tract) and an interesting case of follicular neoplasm of thyroid. Conclusion: Cytology has a high efficacy of diagnosis in patients with cervical lymphadenopathy. It also has the advantage of being able to predict the primary site (where origin of the tumor is unknown) in many cases. It should be considered as an important component of preoperative/pretreatment diagnosis.